2020
DOI: 10.1111/acel.13104
|View full text |Cite
|
Sign up to set email alerts
|

A high‐fat diet reverses metabolic disorders and premature aging by modulating insulin and IGF1 signaling in SIRT6 knockout mice

Abstract: Mammalian sirtuin 6 (SIRT6) is involved in the regulation of many essential processes, especially metabolic homeostasis. SIRT6 knockout mice undergo premature aging and die at age ~4 weeks. Severe glycometabolic disorders have been found in SIRT6 knockout mice, and whether a dietary intervention can rescue SIRT6 knockout mice remains unknown. In our study, we found that at the same calorie intake, a high‐fat diet dramatically increased the lifespan of SIRT6 knockout mice to 26 weeks (males) and 37 weeks (femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…IGF-1 can serve as a monitoring signal that allows reproductive events to occur when the nutritional status for successful reproduction has been reached ( Velazquez et al., 2008 ; Bowman et al., 2010 ). In addition, IGF-1 can stimulate the growth of skeletal muscle through the direct or indirect regulation of protein, lipid and carbohydrate metabolism ( Li et al., 2020c ). The increased expression level of IGF- 1 by daidzein may be attributed to the elevated serum oestrogen concentration since the nuclear receptor (oestrogen receptor) activated by oestradiol has been reported to stimulate the local synthesis of IGF-1 ( Klotz et al., 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1 can serve as a monitoring signal that allows reproductive events to occur when the nutritional status for successful reproduction has been reached ( Velazquez et al., 2008 ; Bowman et al., 2010 ). In addition, IGF-1 can stimulate the growth of skeletal muscle through the direct or indirect regulation of protein, lipid and carbohydrate metabolism ( Li et al., 2020c ). The increased expression level of IGF- 1 by daidzein may be attributed to the elevated serum oestrogen concentration since the nuclear receptor (oestrogen receptor) activated by oestradiol has been reported to stimulate the local synthesis of IGF-1 ( Klotz et al., 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…The pro‐inflammatory response of adipose tissue manifests a shift from storing to releasing fatty acids (Faty et al, 2012; Zhang et al, 1996). In addition to their role as major sources of cellular fuel, fatty acids can serve as signaling molecules exerting adverse effects on cell function, including interference with insulin signaling (Li et al, 2020). The mRNA levels of inflammatory cytokines as well as activation of NF‐κB was decreased in the WAT of TG old mice compared with WT old mice.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue and cell samples were prepared in middle RIPA lysis buffer (Biomiga), supplemented with a cocktail of protease (AbMole Bioscience) and phosphatase inhibitors (Solarbio). Western blotting was performed as described previously before (Li et al, 2020). An equal amount of protein was run on 10% SDA‐PAGE and then transferred to a polyvinylidene difluoride (PVDF) membrane (Millipore).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have demonstrated that free fatty acid with divergent acyl chain length activates SIRT6 deacetylation by competitively inhibiting the peptide-conjugated myristoyl chain and occupying the hydrophobic pocket of SIRT6 [109]. Klein et al investigated 64 fatty acids along with 190 bioactive lipids for initial targeted screening to identify selective SIRT6 activators, and they found that many of them stimulated SIRT6 with 5-to 12-fold activation [110]. They further identified a SIRT6 activator with more potency and selectivity through a SAR-guided chemical optimization study, where the activation of SIRT6 was mediated through the acceleration of catalytic step transpiring after substrate binding but before NAD+ cleavage [109].…”
Section: Fatty Acidsmentioning
confidence: 99%
“…Free fatty acids comprising 12 to 18 carbons were capable of enhancing SIRT6 deacetylation activity up to 35-fold [109]. One study found that, in SIRT6 knockout mice, intake of a high-fat diet could reverse metabolic disorders and premature aging, because fatty acids might be a better energy source to switch the physiological mechanisms [110]. SIRT6 can control circadian chromatin recruitment of SREBP-1, which regulates genes implicated in fatty acid metabolism.…”
Section: Fatty Acidsmentioning
confidence: 99%